ANAVEX®2-73 (blarcamesine), a Sigma-1 receptor agonist, ameliorates neurologic impairments in a mouse model of Rett syndrome - Kaufmann, Walter E.; Sprouse, Jeffrey; Rebowe, Nell; Hanania, Taleen; Klamer, Daniel; Missling, Christopher U. (Pharmacology, biochemistry and behavior, 2019)
Rett syndrome (RTT) is a severe neurodevelopmental disorder that is associated in most cases with mutations in the transcriptional regulator MECP2. At present, there are no effective treatments for the disorder. Despite recent advances in RTT genetics and neurobiology, most drug development programs have focused on compounds targeting the IGF-1 pathway and no pivotal trial has been completed as yet. Thus, testing novel drugs that can ameliorate RTT's clinical manifestations is a high priority. ANAVEX2-73 (blarcamesine) is a Sigma-1 receptor agonist and muscarinic receptor modulator with a strong safety record and preliminary evidence of efficacy in patients with Alzheimer's disease. Its role in calcium homeostasis and mitochondrial function, cellular functions that underlie pathological processes and compensatory mechanisms in RTT, makes blarcamesine an intriguing drug candidate for this disorder. Mice deficient in MeCP2 have a range of physiological and neurological abnormalities that mimic the human syndrome. We tested blarcamesine in female heterozygous mice carrying one null allele of Mecp2 (HET) using a two-tier approach, with age-appropriate tests. Administration of the drug to younger and older adult mice resulted in improvement in multiple motor, sensory, and autonomic phenotypes of relevance to RTT. The latter included motor coordination and balance, acoustic and visual responses, hindlimb clasping, and apnea in expiration. In line with previous animal and human studies, blarcamesine also showed a good safety profile in this mouse model of RTT. Clinical studies in RTT with blarcamesine are ongoing. •Blarcamesine effects in a clinically-relevant mouse model of Rett syndrome.•Blarcamesine improved multiple sensory and motor phenotypes in Mecp2 deficient mice.•Blarcamesine’s effects in young Mecp2 deficient mice were dose-dependent•Blarcamesine’s effects in Mecp2 deficient mice were greatest on hindlimb clasping, a model of hand stereotypies in Rett syndrome.